Essays on applied econometrics - FARIAS, Lucicleyton Henrique de (2023)
This thesis contributes to the recent and evolving field that studies the intersection between the judicial system and individuals’ socioeconomic outcomes. Leveraging the power of econometric models and using a unique dataset comprising criminal cases and extensive administrative data sources from Brazil, this research aims to address two crucial questions that hold significant policy implications. Chapter 1. Conviction, Employment, and Recidivism: Evidence from Brazil This paper examines the impact of a criminal conviction on labor market outcomes and recidivism in Brazil, using an instrumental variable approach. Our findings show a criminal conviction significantly reduces employment by 22 percent, and earnings by 25 percent within three years after the case starts. We also find evidence that a criminal conviction increases following criminal activity by 13 percentage points. Our heterogeneity analysis shows that these adverse effects are concentrated among individuals charged with low-severity crimes. These results suggest that social stigma might play a significant role in the negative consequences of criminal records on labor market prospects. Our study provides the first causal evidence of the direct effects of a criminal conviction on labor and recidivism outcomes in a non-developed country context. Keywords: Instrumental Variable; Random Assignment; Crime; Brazil; Conviction; Chapter 2. Conviction’s Echo: Unveiling Family Consequences in Brazil This paper employs an instrumental variable approach to investigate the impact of an individual’s conviction on labor market outcomes, criminal behavior, and education among family members in Brazil. Our findings reveal compelling evidence of significant reductions in labor market performance for affected family members across both extensive (employment rates) and intensive (earnings) margins. Additionally, our analysis demonstrates conviction increases subsequent criminal activity, particularly in relation to serious offenses. While adverse effects on educational outcomes were estimated, the results did not yield statistical significance. Furthermore, hetero- geneity analysis shows adverse effects are concentrated among males and siblings. This study provides the first causal evidence of the consequences stemming from individual’s conviction on family members in Brazil. By establishing a causal link, it offers compelling evidence of the far-reaching impact of such convictions, shedding light on the pervasive nature of the consequences involved.